Catalytic Synthesis of α-Aminonitriles Using Nano Copper Ferrite CuFe2O4 under Green Conditions. (12th March 2014) - Gharib, Ali; Noroozi Pesyan, Nader; Vojdani Fard, Leila; Roshani, Mina
Abstract : Copper ferrite nanomaterial C u F e 2 O 4 as reusable heterogeneous initiator in the synthesis of α -aminonitriles. The nanocatalyst is easily recovered and its reusability is recorded. Synthesis of α -aminonitriles derivatives by one-pot reaction of different aldehydes with amines and trimethylsilyl cyanides has been developed using nano copper ferrite C u F e 2 O 4 catalyst under room temperature and green solvent (water as solvent) conditions. α -aminonitriles are important in preparing a wide variety of amino acids, amides, diamines, and nitrogen containing heterocycles.